Coherent summation of wake fields excited by an electron bunch sequence in a planar multimode dielectric resonator - Onishchenko, N.I.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2006)
The possibility of realization of resonator concept of dielectric wake field accelerator is studied. The requirements
of implementation of this concept are obtained. Numerical simulations of wake field excitation in planar dielectric
resonator by bunch sequence testify the obtained requirements are true. Исследована возможность реализации концепции ускорителя на кильватерных полях в диэлектрическом резонаторе. Аналитически определены условия когерентного сложения кильватерных полей последовательности электронных сгустков. Проведенное численное моделирование подтверждает условия когерентности. Досліджено можливість реалізації концепції прискорювача на кільватерних полях у діелектричному
резонаторі. Аналітично визначені умови когерентного додавання кільватерних полів послідовності
електронних згустків. Проведене чисельне моделювання підтверджує умови когерентності.